Global Environmental Governance: the Case for a New Paradigm - Padmakumara, S.C; Madurangi, W.D (My University, 2011)
Concurrent to the rapid increase in environmental problems, the politico-institutional framework conditions for environmental policy making and governance are experiencing a major transformation. When defining Global Environment Governance firstly, a few words concerning the phrase need clarification. Governance is about how decisions and policies are being made, who is responsible, how they carry out their mandates, and how they are accountable (El-Ashry, 2005). Environmental Governance in a global, regional or national context emphasizes the necessity of accumulating policy instruments, organizations, rules, procedures and norms to regulate the process of global environmental protection (Najam, Papa, & Taiyab, 2006). Within this context of the global environmental politics and policy, the end goal of global environmental governance is to improve the state of environment and to eventually lead to the broader goal of achieving a sustainable development. However, the global environmental trends continue to be negative and the resources and competency to address these issues have not properly been materialized. Hence, the challenge before us in the contemporary developments of environment protection is to resolve the paradox of achieving high development goals with low environmental degradation through proper environmental governance mechanism.